Reduced TCR Signaling Contributes to Impaired Th17 Responses in Tolerant Kidney Transplant Recipients. Issue 1 (January 2018) - Nova-Lamperti, Estefania; Romano, Marco; Christakoudi, Sofia; Runglall, Manohursingh; McGregor, Reuben; Mobillo, Paula; Kamra, Yogesh; Tsui, Tjir-Li; Norris, Sonia; John, Susan; Boardman, Dominic A.; Lechler, Robert I.; et al.
Abstract : Background: The development of spontaneous kidney transplant tolerance has been associated with numerous B cell–related immune alterations. We have previously shown that tolerant recipients exhibit reduced B-cell receptor signalling and higher IL-10 production than healthy volunteers. However, it is unclear whether cluster of differentiation (CD)4 + T cells from tolerant recipients also display an anti-inflammatory profile that could contribute to graft maintenance. Methods: CD4 + T cells were isolated from kidney transplant recipients who were identified as being tolerant recipients, patients with chronic rejection or healthy volunteers. CD4 + T cells from the 3 groups were compared in terms of their gene expression profile, phenotype, and functionally upon activation. Results: Gene expression analysis of transcription factors and signalling proteins, in addition to surface proteins expression and cytokine production, revealed that tolerant recipients possessed fewer Th17 cells and exhibited reduced Th17 responses, relative to patients with chronic rejection or healthy volunteers. Furthermore, impaired T-cell receptor signalling and altered cytokine cooperation by monocytes contributed to the development of Th17 cells in tolerant recipients. Conclusions: These data suggest that defective proinflammatory Th17 responses may contribute to the prolonged graft survival and stable graft function, which is observed in tolerant recipients in the absence of immunosuppressive agents. Abstract : Tolerant kidney transplanted patients possess fewer Th17 cells and exhibit reduced Th17 responses, relative to patients with chronic rejection or healthy volunteers. Furthermore, impaired TCR signaling and altered cytokine production by monocytes contributes to defective proinflammatory Th17 responses in tolerant recipients. Supplemental digital content is available in the text.